Second language writing anxiety among high proficiency tertiary level students in UiTM Melaka / Canne Paul - Paul, Canne (Faculty of Education, 2010)
Learners of second language experienced certain levels of anxiety in their writing process. It has been proven by researcher in the field of language acquisition ·that anxiety affects the learning process especially those who are of low proficiency level in the target language. This study however, focused on high proficiency tertiary level students particularly in their writing so as to find out the physical, cognitive and affective effects of L2 writing anxiety as well as its causes that affect the students' performance. This study was partially adopted from Atay and Kurt (2006) L2 writing anxiety among prospective teachers of English. A questionnaire, Second Language Writing Anxiety Inventory (SLWAI) which was developed by Cheng (2004) and an open-ended questionnaire which was developed by Atay and Kurt (2006) were used in collecting the data so as to meet the quantitative and qualitative nature of this study. New physical symptoms of L2 writing anxiety such as dryness in the throat and frequent eyes blinking were discovered in the study. Other than that, it was proven that jumbled thoughts and feelings of worry, uneasiness and fear were among the cognitive and affective effects of L2 writing anxiety among the students. As for the causes, it was found that time constraint, certain situations such as test and exams, certain people such as lecturers and smarter classmates, as well as other difficulties such as lack of knowledge in grammar and vocabulary were proven to trigger anxiety among the students.